Long non-coding RNA NEAT1 inhibits oxidative stress-induced vascular endothelial cell injury by activating the miR-181d-5p/CDKN3 axis - Min Zhang; Xueting Wang; Jing Yao; Zhaohui Qiu (Artificial Cells, Nanomedicine, and Biotechnology, 2019)
Endothelial cell (EC) dysfunction induces atherosclerotic coronary heart disease (CHD) development. Recent studies demonstrated that lncRNA NEAT1 mediates multiple biological functions of cells. How NEAT1 regulates EC function is still unclear, so this study explored the role and mechanism of NEAT1 in oxidative stress-induced ECs. The levels of NEAT1 and miR-181d-5p were measured in serum samples from ApoE−/− mice and t-BHP-treated human umbilical vein endothelial cells (HUVECs) by qRT-PCR. The potential role of NEAT1 in viability, migration and apoptosis was analyzed by CCK-8, cell metastasis, flow cytometry, dual-luciferase reporter, RNA immunoprecipitation and Western blot assays using HUVECs overexpressing NEAT1. The expression of NEAT1 was increased, but miR-181d-5p expression was decreased in serum samples from both ApoE−/− mice and t-BHP-treated HUVECs. Overexpression of NEAT1 increased viability, migration and CDKN3 expression but decreased apoptotic rates, caspase-3 activity and miR-181d-5p expression in HUVECs. In addition, NEAT1 acted as a promoter of the proangiogenic capacity of HUVECs by targeting miR-181d-5p/CDKN3. Altogether, these findings indicate that NEAT1 may exert a protective effect on HUVECs by regulating the miR-181d-5p/CDKN3A axis.